Methemoglobinemia in Patient with G6PD Deficiency and SARS-CoV-2 Infection - Palmer, Kieran (Emerg Infect Dis, 2020)
We report a case of intravascular hemolysis and methemoglobinemia, precipitated by severe acute respiratory syndrome coronavirus 2 infection, in a patient with undiagnosed glucose-6-phosphate dehydrogenase deficiency. Clinicians should be aware of this complication of coronavirus disease as a cause of error in pulse oximetry and a potential risk for drug-induced hemolysis.